DEGRADATION OF SOLAR CELLS PARAMETERS FABRICATED ON THE BASIS OF Cu(In,Ga)Se2 SEMICONDUCTOR SOLID SOLUTIONS UNDER ELECTRON IRRADIATION - A. V. Mudryi; N. Refahati; V. D. Zhivulko; M. V. Yakushev; R. W. Martin (Приборы и методы измерений, 2015)
Polycrystalline Cu(In,Ga)Se2 (CIGS) thin films were grown on molybdenum-coated soda-lime glass substrates by co-evaporation of the elements Cu, In, Ga and Se from independent sources. The effect of electron irradiation on the electrical and optical properties of CIGS thin films and solar cells with the structure ZnO:Al/i-ZnO/CdS/CIGS/Mo/glass was studied. It was found that the degradation of the electrical parameters of solar cells (open-circuit voltage, short-circuit current density and efficiency) took place due to the formation of radiation defects (recombination centers) with deep energy levels in the bandgap of CIGS. It was revealed that after electron irradiation intensity of near band-edge luminescence band at about 1,1 eV decreased considerably and bands of luminescence with maxima at 0,93 and 0,75 eV appeared.